2021
DOI: 10.1126/scitranslmed.abb6731
|View full text |Cite
|
Sign up to set email alerts
|

Dual role of endothelial Myct1 in tumor angiogenesis and tumor immunity

Abstract: The cross-talk between angiogenesis and immunity within the tumor microenvironment (TME) is critical for tumor prognosis. While pro-angiogenic and immunosuppressive TME promote tumor growth, anti-angiogenic and immune stimulatory TME inhibit tumor progression. Therefore, there is a great interest in achieving vascular normalization to improve drug delivery and enhance antitumor immunity. However, anti–vascular endothelial growth factor (VEGF) mechanisms to normalize tumor vessels have offered limited therapeut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 81 publications
(94 reference statements)
1
44
0
Order By: Relevance
“…In addition, a recent study has shown that genetic deletion of Myct1, a direct target gene of ETV2, was sufficient to normalize tumor vessels and induce TU-HEV formation in subcutaneous sarcoma, concomitant with antitumoral immunity. Myct1 deletion combined with immunotherapy was successful in increasing long-term survival in anti-PD1 refractory breast cancer model (120).…”
Section: Immune Cells Regulate Hev Neogenesis In Tumorsmentioning
confidence: 97%
“…In addition, a recent study has shown that genetic deletion of Myct1, a direct target gene of ETV2, was sufficient to normalize tumor vessels and induce TU-HEV formation in subcutaneous sarcoma, concomitant with antitumoral immunity. Myct1 deletion combined with immunotherapy was successful in increasing long-term survival in anti-PD1 refractory breast cancer model (120).…”
Section: Immune Cells Regulate Hev Neogenesis In Tumorsmentioning
confidence: 97%
“…This has been attributed to a splicing variant involving exon 7 and has implications for anti-angiogenic cancer therapies [99]. Even recently, Myct1 was identified as a transcription factor in the tumor endothelium and was shown to play a dual role in tumor angiogenesis and tumor immunity [100]. In summary, these studies provide an overview of the emerging rationale and approaches for targeting RNA sensors to decrease angiogenesis, enhance vascular normalization, and improve the antitumor immune microenvironment.…”
Section: How Can We Target Nucleic Acid Sensors To Diminish Tumor Angiogenesis?mentioning
confidence: 99%
“…In recent years, thanks to molecular biology, several therapeutic strategies in cancer diseases have been developed against neoangiogenesis. 70 Previous studies analysed the transcriptome of about thousands RCC patients, and highlighted the existence of seven distinct molecular renal cancer subgroups with different angiogenesis, immune, cell cycle, metabolism and stromal programs. The study of the different genetic mutations underlying neoangiogenesis was then applied to the various therapeutic approaches available today.…”
Section: Renal Cell Carcinomamentioning
confidence: 99%